Vind: A Blockchain-Enabled Supply Chain Provenance Framework for Energy Delivery Systems - Bandara, Eranga; Shetty, Sachin; Tosh, Deepak; Liang, Xueping (Frontiers in Blockchain, 2021)
Enterprise-level Energy Delivery Systems (EDS) depend on different software or hardware vendors to achieve operational efficiency. Critical components of these systems are typically manufactured and integrated by overseas suppliers, which expands the attack surface to adversaries with additional opportunities to infiltrate into EDS. Due to this reason, the risk management of the EDS supply chain is crucial to ensure that we are knowledgeable about the vulnerabilities in software and hardware components that comprise any critical part, quantifiable risk metrics to assess the severity and exploitability of the attack and provide remediation solutions that can influence prioritized mitigation plan. There is a need to realize cyber supply chain risk management for Industrial Control Systems hardware, software, and computing and networking services associated with Bulk Electric System (BES) operations. This paper proposes a blockchain-based cyber supply chain provenance platform ("Vind") for EDS to realize data provenance in a cyber supply chain ecosystem.